Tinjauan Analisis Keyakinan Hakim Kasus Tindak Pidana Korupsi Timah Dalam Mengambil Keputusan Nomor : 70/Pid.Sus-TPK/2024/PN.Jkt.Pst. DAN NOMOR: 1/PID.SUS-TPK/2025/PT DKI - Aditya Nugroho; Rr Lyia Aina Prihadiati (PT Elaborium Elevasi Indonesia, 2026)
A judge's conviction is a judge's inner judgment after reviewing and considering all valid evidence and facts during a trial. Judges must be confident when assessing and deciding a criminal's guilt based on the evidence and facts presented at trial. The difference in judges' convictions in making a decision is due to their independence in assessing the facts and proving the defendant's guilt. The independence of judges in carrying out their duties, as stipulated in Article 24, Paragraph 1 of the 1945 Constitution, states that the judiciary is an independent authority, independent of the influence of the legislative and executive branches. Judges, in carrying out their duties, are free from extrajudicial influences, including bribery, nepotism, public pressure, and even government intervention.Judges differ in their decision-making on a case, influenced by the legal background and approach used, whether normative, empirical, or empirical-normative, in their legal reasoning. However, as long as a judge's decision is based on legal evidence and applicable norms, it cannot be challenged.